Analisis Penerapan Prinsip Keadilan dalam Pemberian Hukuman pada Kasus Tindak Pidana Korupsi Berdasarkan Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi - Krisnawati, Krisnawati; Aji, Rihantoro Bayu (Law and Humanity, 2025)
This research aims to analyze the application of the principles of justice in administering sentences in cases of criminal acts of corruption based on Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. Based on a thematic analysis of court decisions, it was found that there were significant disparities in sentences in corruption cases, especially those involving public officials. Factors such as political influence, public pressure, and judges' interpretation of the severity of criminal acts are the main causes of this injustice. In addition, light sentences are often disproportionate to the loss to the state, giving rise to public dissatisfaction and weakening confidence in the justice system. To increase the application of the principles of justice, this research suggests several efforts, including the preparation of more detailed sentencing guidelines, strengthening the independence of judicial institutions, and increasing the transparency of the legal process. These findings show the importance of balancing justice, legal certainty and expediency in administering punishments for corruption cases. Thus, implementing the principles of justice can provide a more effective deterrent effect while restoring public trust in the Indonesian legal system.